Digital Education before Covid 19 in the administrative economic area - Sánchez Sulú, Nancy Verónica; Peraza Pérez, Limberth Agael; Baqueiro López, Perla Gabriela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this work is to analyze the impact of adaptive learning forced by Covid-19 at the Faculty of Administrative Economic Sciences of the Autonomous University of Carmen. For this study, we approach the theoretical concepts with a documentary review, subsequently a descriptive analysis of a sample of 291 students was made. The results show that most of the students developed a satisfactory performance, preferably using the Teams platform, although platforms were also used as support. This concludes that the university community quickly adapted to the virtual environment imposed by the pandemic.